Genotypic profile of Staphylococcus spp., Enterococcus spp., and E. coli colonizing dogs, surgeons, and environment during the intraoperative period: a cross-sectional study in a veterinary teaching hospital in Brazil - Mareliza Possa de Menezes; Marita Vedovelli Cardozo; Natália Pereira; Mariana Bugov; Newton Valerio Verbisck; Vanessa Castro; Alessandra Figueiredo de Castro Nassar; Paola Castro Moraes (BMC Veterinary Research)
Abstract Aims This prospective cross-sectional study aimed to determine the occurrence of resistance genes and genetic diversity in Staphylococcus spp., Enterococcus spp., and Escherichia coli isolated from dogs' superficial surgical site (SS), surgeons' hands, and the operating room (OR) during the intraoperative period. Methods Thirty dogs undergoing clean/clean-contaminated (G1, n = 20) and contaminated surgeries (G2, n = 10), along with eight surgeons, were included in the study. Specimens were collected using sterile swabs, transported in 0.1% peptone salt solution, and spread onto blood agar. Environmental samples were collected through passive exposure using BHI agar plates. Seventy-five isolates were selected and classified using MALDI-TOF MS. Resistance genes were screened via PCR: tet(M), ermA, aacA-aphD, blaZ, mecA, bla TEM-1, bla SHV, bla SHV-1, bla CTX-M-1, 3 e 15, bla CTX-M-2, bla CMY-2, mcr 1, mcr 2, mcr 3, mcr 4, and ndm. Genetic diversity was assessed through PFGE analysis using SmaI and XbaI restriction enzymes, with clustering performed by the UPGMA method. The chi-square test compared the frequency of resistance gene detected. Results Staphylococcus pseudintermedius (83.33%), Enterococcus spp. (52.63%), and E. coli (62.50%) were more frequently isolated from dogs' skin, while coagulase-negative staphylococci (CoNS; 62.50%) were more frequent in the OR. Resistance genes detected in Staphylococcus spp. included blaZ (79.17%), mecA (43.75%), tet(M) (41.67%), and aacA-aphD (25%). Among Enterococcus spp., tet(M) (78.95%) and blaZ (10.53%) were identified. S. pseudintermedius harbored tet(M) and aacA-aphD genes more frequently than CoNS. No E. coli isolates tested positive for the investigated genes. Twenty-four PFGE banding patterns were observed in CoNS (24/24), 15 in S. pseudintermedius (15/24), 4 in E. coli (4/8), and 7 in Enterococcus spp. (7/19). Genetically related S. pseudintermedius and E. coli were obtained from SS and OR in G2. Seven indistinguishable Enterococcus spp. were identified across different procedures and patients. Conclusion Our study revealed high rates of methicillin-resistant Staphylococcus spp. and tetracycline-resistant Enterococcus spp. colonizing the environment in a veterinary teaching hospital in Brazil. PFGE analysis indicated a high diversity of CoNS and Enterococcus spp. Genetically related strains in S. pseudintermedius, Enterococcus spp., and E. coli emphasize the importance of effective infection control policies to minimize the spread of resistant bacteria.